2016
DOI: 10.1039/c5ta09873d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of morphological degradation of P3HT:PCBM bulk heterojunction films exposed to long-term host solvent vapor

Abstract: A solvent atmosphere results in the degradation of P3HT:PCBM solar cells due to the formation of large PCBM crystallites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 71 publications
3
54
0
Order By: Relevance
“…This hypothesis is in good agreement with the conclusion drawn from the absorption data. The P3HT lattice constants range from 1.7 to 1.8 nm in both directions, which matches values reported usually . From the full‐width‐at‐half‐maximum of the (100) Bragg peak, the corresponding crystal sizes are roughly estimated from the Scherrer equation (Table S1, Supporting Information).…”
Section: Resultssupporting
confidence: 78%
“…This hypothesis is in good agreement with the conclusion drawn from the absorption data. The P3HT lattice constants range from 1.7 to 1.8 nm in both directions, which matches values reported usually . From the full‐width‐at‐half‐maximum of the (100) Bragg peak, the corresponding crystal sizes are roughly estimated from the Scherrer equation (Table S1, Supporting Information).…”
Section: Resultssupporting
confidence: 78%
“…The absorption coefficient was calculated using the equation: ε=A·ln10/L, where A is the absorbance and L is the film thickness [31]. The λ max and ε of P3HT were 519 nm and 5.22 × 10 5 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, because of its small absorption range (below 650 nm) and edge-on crystalline structure, P3HT is known to be inefficient for electron transfer in OPVs [31,32]. Sharma et al expanded the absorption range by adding diketopyrrolopyrrole (DPP)-based conjugated small molecule sensitizers to the photoactive layer in order to enhance the PCE [20].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that prolonging the annealing time resulted in the enhancement of the vertical segregation of the PCBM phase and possibly lead to the formation of µm-sized PCBM aggregates which considerably increased the charge recombination rate. [33][34][35][36][37][38] In our case, since PCBM aggregates are not observed at the BHJ surface, maybe because of the too short annealing time, we considered an alternative approach consisting of washing the BHJ film with dichloromethane (DCM) in order to dissolve PCBM without affecting the P3HT morphology. Therefore, we expected the appearance of cavities in the film morphology Supplementary Information Figure S4).…”
Section: Influence Of the Thermal Annealing Sequence On The Bulk Hmentioning
confidence: 99%